(untitled) (Proceedings of International Conference on Special Education, 2022)
Teachers’ efficacy in catering diverse students’ learning needs in Inclusive Education (IE) Programme classrooms is crucial to determine the successfulness of its implementation. The purpose of this study is to identify the difference on the level of teachers’ efficacy towards IE Programme classrooms across teachers’ groups (special education and mainstream teachers) as some oversea studies showed the level of teachers’ efficacy towards IE Programme classrooms teaching depended on the types of teachers. A set of questionnaire with 11 items on Teachers’ Sense of Efficacy Scale (TSES) in Malaysian context has been distributed to 267 teachers (mainstream: 217 and special education: 50) from 21 public primary schools with IE Programme. The findings indicated that special education teachers had higher mean scores than mainstream teachers in both of the factors, pedagogy efficacy (TE1) and management efficacy (TE2). However, the multivariate tests in MANOVA demonstrated that teachers’ groups (special education and mainstream teachers) had no significant effect towards the level of TE1 and TE2. Therefore, there is no evidence that special education teachers are more efficient than mainstream teachers in IE classrooms. Therefore, well-planned teacher education and professional development programmes are needed to equip both types of teachers with the knowledge and competencies that are required, and also to ensure them to come to a consensus in implementing IE Programme in Malaysia.